Review of Scanning Transmission of High Voltage Electron Microscope - Sura Allawi Obaid; Jenan Hussein Taha (Genius Journals, 2022)
A "cathode lens" against a powerful electric field is formed directly over the sample surface from the scanning electron microscope sample with huge negative bias. This arrangement represents a appropriate system for monitoring the falling the electrons energy to reach units or even fractions of electron volts against just a simple reset of the segment. Furthermore, the field accelerates the wave electrons and balances them with grounded detectors at the top and bottom of the sample, ensuring great collection efficiency and huge intensification of the copy wave. An important characteristic is the capability to obtain the full radiation of scattered electrons, containing those emitted from large angles regarding the normal surface. The energy of the falling electrons is proportional to the deflections of the cathode lens, so the size of the area is approximately constant by total energy parameters. Also, scattered electron images provide improved information about crystal and electronic structures at lower energies and the final fine distribution obtained, with the help of contrast structures which are not elseways available. Also, experiments with diverse materials science areas along previous research are illustrated
Keywords: Low Energy SEM; Low Energy STEM; Scanning Electron; Cathode Lens